The in vitro Photoinactivation of Helicobacter pylori by a Novel LED-Based Device - Morici, Paola; Battisti, Antonella; Tortora, Giuseppe; Menciassi, Arianna; Checcucci, Giovanni; Ghetti, Francesco; Sgarbossa, Antonella (Frontiers in Microbiology, 2020)
The rise of antibiotic resistance is the main cause for the failure of conventional antibiotic therapy of Helicobacter pylori infection, which is often associated with severe gastric diseases, including gastric cancer. In the last years, alternative non-pharmacological approaches have been considered in the treatment of H. pylori infection. Among these, antimicrobial PhotoDynamic Therapy (aPDT), a light-based treatment able to photoinactivate a wide range of bacteria, viruses, fungal and protozoan parasites, could represent a promising therapeutic strategy. In the case of H. pylori, aPDT can exploit photoactive endogenous porphyrins, such as protoporphyrin IX and coproporphyrin I and III, to induce photokilling, without any other exogenous photosensitizers. With the aim of developing an ingestible LED-based robotic pill for minimally invasive intragastric treatment of H. pylori infection, it is crucial to determine the best illumination parameters to activate the endogenous photosensitizers. In this study the photokilling effect on H. pylori has been evaluated by using a novel LED-based device, designed for testing the appropriate LEDs for the pill and suitable to perform in vitro irradiation experiments. Exposure to visible light induced bacterial photokilling most effectively at 405 nm and 460 nm. Sub-lethal light dose at 405 nm caused morphological changes on bacterial surface indicating the cell wall as one of the main targets of photodamage. For the first time endogenous photosensitizing molecules other than porphyrins, such as flavins, have been suggested to be involved in the 460 nm H. pylori photoinactivation.